So, my problem is this: I have to solve the heat equation with this boundary condition:

$$ \begin{cases} \dfrac{\partial}{\partial t} u(x, t) - D\ \dfrac{\partial^2}{\partial x^2} u(x, t) = S_0\delta(x)\delta(t) \\\\ u(x, 0) = U_0\delta(x) \end{cases} $$

Where $D, U_0, S_0$ are coefficients.

So the first step was to perform a Fourier transform on the whole equation (on $x \to k$) to get

$$\hat u (k, t) + D k^2 \hat u(k, t) = S_0 \delta(t)$$

And it's ok.

But then in the paper it's written that a Laplace transform (on $t\to s$) is performed, getting:

$$s\ \hat{\tilde u}(k, s) - U_0 + D k^2 \hat{\tilde u} (k, s)= S_0$$

Where of course $s$ (and before: $k$) are the new variables obtained because of the transformations.

My question is: Where does the $U_0$ term comes from, in the Laplace transform?

I cannot find a way to get it, I don't understand how it comes out.


Ok, it comes out by LT. But I got stuck in computing it. Shalln't it be also an anti transform? Anybody can help me with the calculation?

  • $\begingroup$ The constant comes from the Laplace transform of $\hat{u}_{t}$. Integrate by parts and use your initial condition from your PDE transformed into Fourier space. $\endgroup$
    – mattos
    Nov 21, 2016 at 14:03
  • $\begingroup$ @Mattos Indeed that is right. The other problem is: how does it come out? I think I got stuck in performing the LT! (Which actually shall be an ANTI transform... right? $\endgroup$
    – Laplacian
    Nov 21, 2016 at 14:08
  • $\begingroup$ I'll make a post. $\endgroup$
    – mattos
    Nov 21, 2016 at 14:08
  • $\begingroup$ @Mattos Wow, thank you super much!! $\endgroup$
    – Laplacian
    Nov 21, 2016 at 14:09
  • 3
    $\begingroup$ @Betty Let $\tilde{\hat{u}}(k,s)=\tilde{v}(k,s)$, then we have $$-U_{0}+s\tilde{v}+Dk^{2}\tilde{v}=S_{0} \implies \tilde{v}=\frac{S_{0}+U_{0}}{s+Dk^{2}}$$ and taking the inverse Laplace transform of both sides gives \begin{align} \mathcal{L}^{-1}\{\tilde{v}(k,s)\}&=v(k,t) \\ &=\mathcal{L}^{-1} \left(\frac{S_{0}+U_{0}}{s+Dk^{2}}\right) \\ &=(S_{0}+U_{0})\mathcal{L}^{-1} \left(\frac{1}{s-(-Dk^{2})}\right) \\ &=(S_{0}+U_{0})\exp\left(-Dk^{2}t\right) \end{align} where in the second to last lines we have $$\mathcal{L}^{-1} \left(\frac{1}{s-a}\right)=\exp(at)$$ $\endgroup$
    – mattos
    Apr 11, 2019 at 10:58

1 Answer 1


Laplace transforming your equation

$$\hat{u}_{t}(k,t) + D k^{2} \hat{u}(k,t) = S_{0} \delta(t)$$


\begin{align} \int_{0}^{\infty} \hat{u}_{t} e^{-st} dt + D k^{2} \underbrace{\int_{0}^{\infty} \hat{u} e^{-st} dt}_{D k^{2} \tilde{\hat{u}}} &= S_{0} \underbrace{\int_{0}^{\infty} \delta(t) e^{-st} dt}_{1} \\ \\ \implies \hat{u} e^{-st} \bigg|_{0}^{\infty} + s \underbrace{\int_{0}^{\infty} \hat{u} e^{-st} dt}_{\tilde{\hat{u}}} + D k^{2} \tilde{\hat{u}} &= S_{0} \end{align}

where we used integration by parts on the first integral with $v = e^{-st}$, $w' = \hat{u}_{t}$. Then note that

\begin{align} \lim_{t \to \infty} \hat{u}(k,t) e^{-st} &\to 0 \\ \hat{u}(k,t) e^{-st} \bigg|_{t = 0} &= \hat{u}(k,0) \\ \end{align}

But $\hat{u}(k,0)$ is just the Fourier transform of our initial condition. The Fourier transform of $\delta(x)$ is $1$ (depending on the convention, I think the transform you are using might have a scaling in front in which case it should actually be $1/\sqrt{2 \pi}$ or $1/2 \pi$). So we get

\begin{align} \hat{u}(k,0) &= U_{0} \\ \implies -U_{0} + s \tilde{\hat{u}} + D k^{2} \tilde{\hat{u}} &= S_{0} \end{align}

  • $\begingroup$ @AlanTuring All good mate. $\endgroup$
    – mattos
    Nov 21, 2016 at 14:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.